Functionalized graphene, method for preparing functionalized graphene and use thereof

By partially reacting the graphene material with silane, functionalized graphene material solves the problem of large amount of dust generation, improves the fluidity and bulk density, and achieves better operating performance and environmental friendliness.

CN115720573BActive Publication Date: 2025-03-11EVONIK OPERATIONS GMBH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202180045863.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-01
Filing Date
2021-06-15
Publication Date
2025-03-11
Estimated Expiration
2041-06-15

AI Technical Summary

Technical Problem

The large amount of dust generated by graphene materials leads to poor operating performance, pollution problems and safety risks, and its low bulk density increases the cost of introducing the matrix system.

Method used

By partially reacting the graphene material with silane, functionalized graphene material improves its fluidity and bulk density, and reduces dust generation.

Benefits of technology

Functionalized graphene materials have significantly better fluidity and higher bulk density, produce less dust, and can be better incorporated into the matrix system, reducing operational and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004019540980000131
    Figure BDA0004019540980000131
  • Figure BDA0004019540980000132
    Figure BDA0004019540980000132
  • Figure HDA0004019540990000011
    Figure HDA0004019540990000011
Patent Text Reader

Abstract

The present invention relates to a method for functionalizing a graphene material by mixing the graphene material with at least one silane, to the functionalized graphene material itself, and to the use thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for functionalizing a graphene material, to the functionalized graphene material itself, and to the use thereof. Background Art

[0002] Graphene, its preparation, properties and applications are discussed in detail in the specialist literature, e.g. Online, https: / / roempp.thieme.de / lexicon / RD-07-02758 middle.

[0003] Similar to graphite, each carbon atom in graphene is covalently linked to three neighboring atoms via σ bonds. The C,C bond length is 142 pm. These atoms are sp 2 hybridized, and the σ bonds lie in one plane. Graphite therefore has a planar structure. Partially filled pz orbitals are retained on each atom. These p z The orbitals are perpendicular to the plane of the bonds and form a delocalized π-electron system which is of primary importance in determining the electronic properties of graphene.

[0004] Crystallographically, graphene can be described by two equivalent sublattices with unit cell vectors The angle between them is 60°. The unit cell consists of two carbon atoms at positions (0,0) and (a / 3,2b / 3) respectively. Therefore, the atomic density is 38.2nm -2 .

[0005] For the purposes of the present invention, the expression "graphene material" means one or more materials according to ISO / TS 80004-13, i.e.

[0006] Graphene,

[0007] ——Graphene-like carbon materials,

[0008] ——Single-layer, double-layer and triple-layer graphene,

[0009] ——Epitaxial graphene,

[0010] ——Exfoliation of graphene,

[0011] ——Few-layer graphene,

[0012] - Multi-layer graphene,

[0013] ——Few-layer nanoribbons,

[0014] ——Graphene nanoplates,

[0015] ——Graphene nanoplatelets,

[0016] ——Graphene nanosheets,

[0017] ——Graphene microsheets,

[0018] ——Graphene nanosheets,

[0019] ——Graphene nanoribbons,

[0020] ——Graphene oxide,

[0021] ——Graphene oxide nanosheets,

[0022] ——Multilayer graphene oxide,

[0023] ——Graphene quantum dots,

[0024] --graphite,

[0025] ——Graphite nanoplates,

[0026] ——Graphite nanosheets,

[0027] ——Graphite nanosheets,

[0028] - graphite oxide,

[0029] ——Reduced graphene oxide,

[0030] or a mixture of these materials.

[0031] Graphene materials can be used in a large number of technical fields.

[0032] For example, CN 109504318 A proposes a method for modifying a polystyrene film for a flexible printed circuit using oxidized graphene and aluminum oxide.

[0033] Patent application WO 2018019905 A1 discloses a method for coating a metal substrate with one or several monolayers of graphene by means of a binder substance.

[0034] WO 2015055252 A1 discloses vinyl silanes which can be used in rubber mixtures containing graphene materials, for example in the manufacture of tires.

[0035] CN 104342003 A proposes a water-based paint for a dustproof and sterilizing glass door. Graphene is particularly used in the preparation of the paint.

[0036] CN 105056879 A teaches how the mechanical properties of asphalt can be improved by a composition comprising polyester fibers and graphene.

[0037] The following concentrate can be used for the preparation of vulcanized rubber mixtures, which contains graphene and sulfonamides in addition to other materials. CN 107459717 A discloses such a concentrate and a method for its preparation.

[0038] Graphene materials are also used to protect building materials from decay. According to the teaching of CN 108947394 A, modified graphene oxide is incorporated into Portland cement in addition to other materials.

[0039] WO 2019145307 A1 discloses a composition comprising polymer inorganic nanoparticles, and the use of the composition in a sliding aid and lubricant on a metal surface. The nanoparticles used include, in particular, graphene.

[0040] Graphene materials are commercially available as powders and often have a very low bulk density, for example in the range of 2 to 400 g / l. In addition to the low bulk density, most graphene materials also have poor flowability and / or generate high dust content during pouring. This leads to poor handling properties and causes problems during weighing and metering, and is also criticized from the perspective of environmental protection and work safety.

[0041] For example, poor handling properties are evident when powders are incorporated into elastomeric systems, as is the case during rubber kneading: the correct point in time and duration of incorporation of the powdered filler is a critical factor in producing a well-filled compounded rubber mass. The filler is poured into the mixing chamber through a hopper and then pushed toward rotating rollers by a pneumatic plunger.

[0042] Although the prior art discloses methods of using silane or siloxane to improve or achieve dispersion of graphene materials or other fillers in a matrix system, this is mainly achieved by using silane in insufficient amounts.

[0043] However, there is a continuing need for a technical operating procedure that is able to handle or avoid the amount of dust generated during the use of powdered graphene materials, because firstly, the dust leads to pollution problems and makes it difficult to measure the amount of filler actually introduced into the matrix system. Secondly, for reasons of work safety and environmental protection, the removal of the dust by suction or by disposal is necessary.

[0044] Furthermore, the dustiness and generally low bulk density of graphene materials increase the costs of introducing said materials into the desired matrix system. Corresponding problems arise, for example, when preparing thermoplastic compounds filled with graphene materials in an extruder. For the reasons mentioned, it is difficult or impossible to ensure that the powdered graphene material is introduced at the right time during the preparation of the thermoplastic system. Summary of the invention

[0045] It is therefore an object of the present invention to process graphene materials into products having improved flowability and / or increased bulk density, which products generate less dust during processing and which products can therefore be better incorporated into commercially interesting matrix systems.

[0046] Surprisingly, it has been found that this object can be achieved using silane-functionalized graphene materials.

[0047] The present invention provides a method for functionalizing a graphene material, the method being characterized in that the graphene material is at least partially reacted with at least one silane, wherein the at least one silane has a structure Y—Si(OR 1 )(OR 2 )(OR 3 ),and

[0048] Y is

[0049] branched or unbranched alkyl groups, olefin groups or aromatic groups, combinations of these groups, or

[0050] a functional organic group selected from carboxyl, carbonyl, hydroperoxycarbonyl, halogen, sulfo, sulfinic acid, hydroxysulfenyl, cyano, formyl, oxo, thioxo, hydroxyl, amino, imino, hydrazine, epoxy, sulfanyl, fluoro, or a combination of these groups; or

[0051] a combination of an alkyl, olefin or aromatic group and said functional organic group, and

[0052] R 1 , R 2 , R 3 are branched or unbranched alkyl, olefin or aromatic groups, and they are identical or different to each other, and

[0053] The at least partial reaction is performed during mixing of the one or more silanes with the graphene material.

[0054] After carrying out the method of the present invention, the graphene material is obtained in the form of particles.

[0055] For the purpose of the present invention, based on Online, https: / / roempp.thieme.de / 35IDR According to the definition of DIN ISO 697:1984-01, the term "granule" means an agglomerate of asymmetric aggregates consisting of powder particles. The aggregates have an uneven surface and do not have a consistent geometric shape. The granules can be characterized by determining the bulk density according to DIN-ISO 697:1984-01 and the angle of repose according to DIN ISO 4324:1983-12.

[0056] The advantage of the method of the invention is that it is very easy to implement and thereby achieves a graphene material that, when compared to conventional graphene materials, generates less dust and has significantly better flowability. Thus, regardless of the dispersion method, added value is achieved when dispersed in different matrix systems.

[0057] The present invention is explained in more detail below.

[0058] It may be advantageous to use two or more silanes in the process of the invention, in which Y or R 1 , R 2 , R 3 Are two identical or different.

[0059] The at least one silane may preferably be selected from:

[0060] 3-glycidyloxypropyltriethoxysilane (abbreviated as GLYEO), 3-aminopropyltriethoxysilane (abbreviated as AMEO), glycidyloxypropyltrimethoxysilane (abbreviated as GLYMO) and 3-aminopropyltrimethoxysilane (abbreviated as AMMO), or a mixture selected from these silanes.

[0061] The at least one silane may more preferably be selected from bis(triethoxysilylpropyl)tetrasulfide, bis(triethoxysilylpropyl)disulfide, 3-thiocyanatopropyltriethoxysilane, γ-aminopropyltriethoxysilane, SIVO 214, γ-aminopropyltrimethoxysilane, bis(triethoxysilylpropyl)amine, bis(trimethoxysilylpropyl)amine, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, triaminofunctional silane, benzylaminosilane (50% MeOH solution), benzylaminosilane (60% aqueous solution), vinylbenzylaminosilane (42%~MeOH solution), vinylbenzylaminosilane (40% aqueous solution), polyazamide silane (Polyazamide Silan) (53% MeOH solution), quaternary ammonium silane (48% aqueous solution), methacrylamidosilane (40% aqueous solution), γ-aminopropylsilanol (40% aqueous solution), γ-aminopropylsilanol (88% aqueous solution), vinylaminoalkylsilanol (60% aqueous solution), VPS 1208, triaminofunctional silanol (40% aqueous solution), 3-ureidopropyl trimethoxysilane, 3-ureidopropyl triethoxysilane (50% methanol solution), 3-ureidopropyl triethoxysilane (containing 10% ethanol), γ-glycidyloxypropyl trimethoxysilane, γ-glycidyloxypropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane (MEMO), γ-methacryloxypropyl triethoxysilane (MEEO), ethyl Vinyltrimethoxysilane (VTMO), vinyltriethoxysilane (VTEO), oligomeric alkyl silane (50% aqueous solution), polyether functional trimethoxysilane, vinyltrimethoxysilane (VTMO), 3-methacryloxypropyltriethoxysilane (MEEO), 3-methacryloxypropyltrimethoxysilane (MEMO), octyltrimethoxysilane (OCTMO), octyltriethoxysilane (OCTEO), or a combination of these silanes.

[0062] All these silanes which can preferably be used are obtainable from Evonik Resource Efficiency GmbH, Rodenbacher Chaussee 4, 63457 Hanau, Germany.

[0063] The silane can particularly preferably be selected from 3-glycidyloxypropyltriethoxysilane (GLYEO), 3-aminopropyltriethoxysilane (AMEO), glycidyloxypropyltrimethoxysilane (GLYMO) and 3-aminopropyltrimethoxysilane (AMMO), or from mixtures of these silanes.

[0064] Glycidyloxypropyltriethoxysilane (GLYEO) can be used with very particular preference.

[0065] In the method of the present invention, the sum of the mass fractions of the at least one silane may be in the range of 0.1 to 70 wt %, preferably 5 to 50 wt %, more preferably 25 to 40 wt %, wherein the sum of the mass fractions of the one or more silanes and the graphene material is 100 wt %.

[0066] If the mass fraction of the one or more silanes used is 50% by weight in total, the weight ratio of graphene material to the one or more silanes present is 1:1.

[0067] In the method of the present invention, the at least partial reaction may be performed at a temperature ranging from 50° C. to 150° C., preferably ranging from 80° C. to 110° C. The temperature may be additionally adjusted depending on the at least one silane, the graphene material and the mode of the mixing process.

[0068] In the method of the present invention, the mixing process may preferably use a mixing granulator, a container with grinding balls, a ball mill, a three-roll mill, a stirrer or a container equipped with paddles.

[0069] In the method according to the invention, the functionalization provides particles without compaction, which have a higher bulk density and compaction density than unfunctionalized graphene materials. This is surprising, since conventional methods for preparing particles usually require compaction. However, it may be advantageous that, in the method according to the invention, compaction can be achieved by the mixing process, for example by using a three-roll mill.

[0070] In the claimed method, if the at least one silane is used in a mass fraction of at least 5% by weight, particularly preferably at least 10% by weight, with or without compaction, more preferably the at least one silane is in a mass fraction range of 0.1% by weight to 70% by weight, preferably 5% by weight to 50% by weight, more preferably 25% by weight to 40% by weight, particles are obtained wherein the sum of the mass fractions of the one or more silanes and the graphene material is 100% by weight.

[0071] Furthermore, it may be advantageous to prepare the at least one silane before the mixing process. Such a preparation is carried out in the examples of the present invention. This preparation enables prefunctionalization of the at least one silane.

[0072] In a preferred manner, a defined amount of the at least one silane can be added to an alcohol-water mixture, particularly preferably to an ethanol-deionized water mixture, very particularly preferably to a mixture of 95% by volume ethanol and 5% by volume deionized water, and the resulting preparation can be stirred at room temperature for a certain period of time, preferably 1 to 100 minutes, particularly preferably for about 10 minutes.

[0073] Furthermore, it may be advantageous to adjust the deionized water to a defined pH value, preferably to a pH value in the range of 4.5 to 5.5, using an acid, preferably HCl. A defined amount of the at least one silane can then be added to the preparation and the resulting preparation can be stirred at room temperature for a certain time, preferably 1 to 100 minutes, particularly preferably for about 10 minutes.

[0074] It may likewise be advantageous to add a defined amount of the at least one silane to ethanol (analytical grade) and to stir the resulting preparation at room temperature for a certain time, preferably 1 to 100 minutes, particularly preferably for about 10 minutes.

[0075] In all these options, it may be advantageous to subsequently obtain a clarified phase.

[0076] The preferred preparation process differs from the conventional process in that only water or a water-ethanol mixture is used for the prefunctionalization.

[0077] For the purposes of the present invention, the expression "room temperature" means a temperature of 20°C.

[0078] As already mentioned, method of the present invention provides functionalized graphene material, and this functionalized graphene material has the packing density and compacted density of increase compared with traditional graphene material.In addition, as shown in the embodiment, the processing of described functionalized graphene material produces significantly less dust.Especially, the functionalized graphene material obtained according to the present invention can be better incorporated into various matrix systems.In addition, the functionalized graphene material obtained according to the present invention can be supplied to these systems faster and / or more simply.

[0079] Furthermore, it is surprising that the flow properties of the graphene materials functionalized according to the invention show surprisingly little change or are better than those of unfunctionalized graphene materials.

[0080] For the purpose of the present invention, by Figure 6 As schematically illustrated in FIG. 1 , a defined amount is added to a drum and the drum is subjected to a uniform rotational motion to determine the flowability. A camera is then used to determine the angle at which the material begins to avalanche. The direction of the rotational motion is Figure 6In each case, the free arrows are shown. The smaller the value of this so-called "avalanche angle" (ava,h) within the scope of the present invention, the greater the fluidity of the material, that is, the better. The "avalanche angle" is the angle between the surface formed by the particles and the horizontal plane (h) at the moment when the avalanche starts. The avalanche angle between (ava) and the horizontal plane (h) is mathematically measured in the positive direction. Detailed information on determining fluidity can be found, for example, in the following paper: Amado, "Advances in SLS powder characterization", 22nd Annual International Solid Freeform Fabrication Symposium-An Additive Manufacturing Conference, SFF, 2011, pp. 438-452.

[0081] It may be advantageous to use a mass fraction of at least 30% by weight of the at least one silane in the process according to the invention. Above such a mass fraction, it was found that the avalanche angle decreases with increasing proportion of the at least one silane. The mass fraction of the at least one silane that can preferably be used is in the range of 30% to 70% by weight, preferably 30% to 50% by weight, more preferably 30% to 40% by weight, wherein the sum of the mass fractions of the one or more silanes and the graphene material is 100% by weight.

[0082] Therefore, the present invention also provides a functionalized graphene material obtained by the method of the present invention.

[0083] Preferably, the functionalized graphene material of the present invention or the functionalized graphene material obtained according to the present invention has a bulk density of 300 g / l to 900 g / l, more preferably 500 g / l to 800 g / l, and / or has a compacted density of 300 g / l to 900 g / l, preferably 500 g / l to 800 g / l, and / or exhibits a reduction in dust generation of 50% to 80%, preferably 55% to 75%.

[0084] For the purposes of the present invention, the bulk density and the pressed density of the graphene materials functionalized according to the invention and of unfunctionalized graphene materials are determined in accordance with DIN 53912 and DIN / ISO 787, respectively.

[0085] For the purposes of the present invention, the dust generation is determined in the rotation method according to DIN 55992 by using a Heubach dust meter type I dust generation device.

[0086] In the examples, the dust generation is measured as the mass of dust generated by the unfunctionalized graphene material and the graphene material functionalized according to the invention. For the purposes of the present invention, the reduction rate of dust generation is the ratio of the following two values, expressed in %:

[0087] - the difference between the dust mass determined for the unfunctionalized graphene material according to DIN 55992 and the dust mass determined for the graphene material functionalized according to the invention, and

[0088] ——Dust mass measured for unfunctionalized graphene material.

[0089] Due to the unchanged or improved flowability with the mass fraction of the at least one silane, which is a further advantage mentioned of the functionalized graphene material according to the invention or the functionalized graphene material obtained according to the invention, the material can be used in at least the same fields of application as the unfunctionalized material, but it can be processed more easily and does not have the disadvantages mentioned for conventional graphene materials.

[0090] The present invention therefore also provides for the use of the functionalized graphene materials according to the invention or the functionalized graphene materials obtained according to the invention as fillers, as corrosion protection in coatings, for anti-icing, as active material and / or electrode material in batteries, in composite materials and / or foams for modifying mechanical, thermal, electrical and tribological properties and flame retardancy, in tire rubbers, in transmission oils and / or engine oils, in metal processing, or in membranes.

[0091] In tire rubbers, the use according to the invention has the advantage of improved thermal and / or electrical properties, as well as improved rolling resistance, wet skid performance and wear. The claimed use in oils improves tribological properties, such as friction, wear and heat dissipation.

[0092] The functionalized graphene material of the present invention or the functionalized graphene material obtained according to the present invention can be preferably used in the following substances:

[0093] - a thermoplastic selected from standard thermoplastics, preferably PE, PP, PS, PVC,

[0094] ——Engineering thermoplastics, preferably PET, PMMA, PC, POM, PA,

[0095] ——High-performance thermoplastics, preferably PPS, PEEK, PES,

[0096] - copolymer, elastomer, preferably silicone, more preferably RTV, HTV, LSR,

[0097] ——Polyurethane, rubber, preferably SBR, BR, natural rubber,

[0098] - Thermosetting plastics, preferably polyurethane, polyester resin, phenolic resin, epoxy resin, acrylate resin, silicone resin,

[0099] - a solvent, preferably an aprotic-nonpolar solvent, an aprotic-polar solvent or a protic solvent,

[0100] - Oil, preferably mineral oil, silicone oil, process oil. DETAILED DESCRIPTION

[0101] The present invention is illustrated below by way of examples.

[0102] Example A: Functionalization of graphene in a flask.

[0103] Silane GLYEO was prepared as follows before use:

[0104] An ethanol-deionized water mixture (95% by volume ethanol, 5% by volume deionized water) in an amount of 3 ppw was adjusted to a pH range of 4.5 to 5.5 with HCl. Then 1 ppw of the silane was carefully added thereto using a syringe, and the mixture was stirred at room temperature for about 10 minutes. This resulted in prefunctionalization of the silane. A clear phase was obtained.

[0105] Graphene oxide was selected as the graphene material. A round-necked flask equipped with a paddle was charged with 4 ppw of graphene oxide and 4 ppw of the prepared clear phase was added. A partial reaction was carried out in a rotary evaporator at 100° C. and at a pressure of 30 hPa for 3 hours.

[0106] The resulting graphene material functionalized according to the invention was then purified from excess silane with ethanol (analytical grade) in a Soxhlet extractor apparatus, predried overnight in a fume hood with the suction system running, and then dried in a rotary evaporator at 100° C. and a pressure of 30 hPa for 3 hours.

[0107] Example B: Functionalization of graphene in a laboratory mixer granulator.

[0108] Silane GLYEO was prepared as follows before use:

[0109] 3 ppw of deionized water was adjusted to a pH range of 4.5 to 5.5 with HCl. 1 ppw of the silane was carefully added thereto using a syringe, and the mixture was stirred at room temperature for about 10 minutes. A clear phase was obtained.

[0110] Graphene oxide was selected as the graphene material. A laboratory mixer granulator was charged with 4 ppw of this graphene material and 4 ppw of the clarified phase. A partial reaction was carried out in a mixing vessel at 100° C. and at a rotation speed of 300 rpm for 3 hours.

[0111] The resulting graphene material functionalized according to the invention was then purified from excess silane with ethanol (analytical grade) in a Soxhlet extractor apparatus, predried overnight in a fume hood with the suction system running, and then dried in a rotary evaporator at 100° C. and a pressure of 30 hPa for 3 hours.

[0112] Example C: Functionalization of graphene in a ball mill.

[0113] Silane GLYEO was prepared as follows before use:

[0114] The apparatus was pre-charged with 3 ppw of ethanol (analytical grade). 1 ppw of the silane was carefully added using a syringe and the mixture was stirred at room temperature for about 10 minutes. A clear phase was obtained.

[0115] Graphene oxide was selected as the graphene material. 4 ppw of this graphene material and 4 ppw of the clarified phase were charged into the grinding container of the ball mill. 4 ppw of grinding balls with a diameter of 2 to 10 mm were additionally added thereto. The partial reaction was carried out in the ball mill at a rotation speed of 600 rpm for 15 minutes.

[0116] The resulting graphene material functionalized according to the invention was then purified from excess silane with ethanol (analytical grade) in a Soxhlet extractor apparatus, predried overnight in a fume hood with the suction system running, and then dried in a rotary evaporator at 100° C. and a pressure of 30 hPa for 3 hours.

[0117] Example D: Functionalization of graphene in a triple roll mill.

[0118] Silane GLYEO was prepared as follows before use:

[0119] The apparatus was pre-charged with 3 ppw of ethanol (analytical grade). 1 ppw of silane was carefully added using a syringe and the mixture was stirred at room temperature for about 10 minutes. A clear phase was obtained.

[0120] Graphene oxide was selected as the graphene material. A glass beaker was charged with 4 ppw of this graphene material and 4 ppw of the clear phase.

[0121] The reaction mixture was homogenized by stirring with a metal spatula. The mixture was then slowly and evenly dispersed onto the rollers of a three-roll mill. The rollers of the mill consisted of SiC and were temperature controlled with the aid of an oil bath to an oil temperature of 100° C. and a surface temperature of 60° C. measured on the rollers. The temperature was monitored using an infrared thermometer.

[0122] The rollers were running at different speeds and directions of rotation, specifically: roller 1 had a speed of 12 rpm, roller 2 at 36 rpm, and roller 3 at 110 rpm. Figure 1 The following table shows the schematic diagram of the process.

[0123] A defined distance was set between the rollers, specifically: the distance between roller 1 and roller 2 was 15 μm, and the distance between roller 2 and roller 3 was 5 μm.

[0124] Here, depending on the amount of material applied, a pressing force of 1 to 6 N / mm is achieved. 2 The material is discharged by a scraper located on the roller 3.

[0125] The resulting graphene material functionalized according to the invention was then purified from excess silane with ethanol (analytical grade) in a Soxhlet extractor apparatus, predried overnight in a fume hood with the suction system running, and then dried in a rotary evaporator at 100° C. and a pressure of 30 hPa for 3 hours.

[0126] Example E: Determination of the properties of the functionalized graphene.

[0127] 1) Dust generation was determined according to DIN 55992-1 (June 2006 edition).

[0128] use Figure 2 The Heubach dust meter I type dust generating device schematically illustrated in FIG. The construction details of such a device are known to those skilled in the art.

[0129] Graphene oxide was selected as the graphene material.

[0130] The amount of dust generated with unfunctionalized graphene material and with graphene material functionalized according to the invention was determined using the rotation method. The standard settings according to DIN 55992-1 were selected:

[0131] 30 rpm

[0132] Air flow rate 20L / min

[0133] 100L

[0134] 5 minutes

[0135] First, the dust generation was determined with different amounts of unfunctionalized graphene material graphene oxide. In the case of a larger amount of graphene material, i.e., a larger starting weight, the amount of dust released was greater, which had a positive effect on the experimental error. However, it was observed that a sample weight that was too high could cause airway blockage in the device, resulting in an underestimated amount of released dust. Such results were discarded. Table 1 shows the results of the determination.

[0136] Table 1. Dust generation of unfunctionalized graphene materials.

[0137]

[0138] The unfunctionalized graphene material releases 3.4% of dust in the case of 5 g sample weight and 3.0% of dust in the case of 7.5 g sample weight. This dust is collected in each case in a filter and weighed. In both determinations, 100 liters of air are sucked through the dust meter for a predetermined time.

[0139] The dust generation was then determined on the functionalized graphene material according to the invention from Example C, and in particular with sample weights of 5 g and 7.5 g of said functionalized graphene material. Table 2 shows the results of the determination.

[0140] Table 2. Dust generation of graphene materials functionalized according to the present invention.

[0141]

[0142] In these experiments, the dust mass determined in the filter was significantly less than the dust mass in the case of the unfunctionalized graphene material. During the measurement using 5 g of the graphene material functionalized according to the invention, 1.0% of dust was released. This corresponds to a reduction of 68% compared to the unfunctionalized graphene material. A similar reduction in dust release of 68% was achieved with a sample weight of 7.5 g.

[0143] 2) Determine bulk density and compacted density.

[0144] The bulk density and the compacted density of the functionalized graphene material according to the present invention and the unfunctionalized graphene material were determined using a tamping volume meter based on DIN 53912 and DIN / ISO 787, respectively. Figure 3 The following table shows the schematic diagram of the process.

[0145] The graphene material functionalized according to the invention contains agglomerates with a diameter below 0.5 mm. These agglomerates were not removed, since this would otherwise have resulted in such a strong loss of quality that a representative analysis of the bulk material would no longer be possible.

[0146] To determine the bulk density, the respective material is slowly added via a funnel into a tared 100 ml measuring cylinder. Once the filling process is complete, wait for 1 minute to allow the air to escape so that the filling level obtained after the air has escaped is constant. The measuring cylinder must be at rest and the filling level must be smoothed as much as possible using a spatula if necessary.

[0147] Once the filling level has been read, the mass of material loaded is determined. The bulk density is calculated by dividing the mass by the filling volume. The density of each material is determined twice. To determine the tapped density, the measuring cylinder is mechanically compacted 1250 times according to DIN / ISO 787.

[0148] The results are shown in Figure 4 In the case of the graphene material functionalized with GLYEO according to the invention, the bulk density exceeds 600 g / l, which is more than 3 times higher than the 177 g / l of the unfunctionalized graphene material. The compacted density of this functionalized graphene material of more than 700 g / l is also more than 3 times higher than the 230 g / l of the untreated graphene. Thus, the method of the invention leads to a more compacted graphene material. In addition, Figure 4 Also given is the "compactness", which is the ratio of bulk density to compacted density, expressed as a percentage.

[0149] Figure 5 The effectiveness of the method according to the invention is shown based on the functional relationship between the packing density of the graphene material functionalized according to the invention and the amount of silane GLYEO used.

[0150] The mass fraction of the silane GLYEO varied between 10% by weight and 50% by weight. Starting from a bulk density of 502 g / l when using 10% by weight of GLYEO, an increase was found to a value of about 650 g / l when using 50% by weight of GLYEO. Figure 5 It can be seen that there is a linear relationship between the proportion of GLYEO and the bulk density.

[0151] 3) Determine fluidity.

[0152] In order to determine the effect of the functionalization of the graphene material according to the invention on its flowability, a Revolution Powder Analyzer, model Rev 2015, from PS Prozesstechnik GmbH was used. Figure 6As shown, a defined amount is added to a rotating drum and a camera is used to determine the angle at which the material begins to avalanche. The smaller the avalanche angle (ava,h), the better the fluidity of the material, which is the angle between the surface formed by the particles and the horizontal plane (h) during avalanche. The avalanche angle is mathematically measured between (ava) and the horizontal plane (h) in the positive direction. The working mode of the powder analyzer and the variables measured with it are known to those skilled in the art. Detailed information on determining fluidity can be found, for example, in the following paper: Amado, "Advances in SLSpowder characterization", 22nd Annual International Solid Freeform FabricationSymposium-An Additive Manufacturing Conference, SFF, 2011, pp. 438-452.

[0153] According to the manufacturer's instructions, 100 ml of material was used in a PET drum with a diameter of 100 mm. To measure the fill volume, the air cushion was removed by shaking rather than compacting, as specified.

[0154] The measuring parameters of the flowability procedure described correspond to the standard settings for dark powders:

[0155] 0.5rpm

[0156] 150 avalanche processes started

[0157] Avalanche threshold 0.65%

[0158] Camera: Shutter speed 6ms, gain 6db (black powder), 10 frames per second

[0159] Figure 7 The average angle of the respective powder surface from 150 avalanches is shown for graphene materials prepared according to the invention with different proportions of silane GLYEO. The larger the angle at the start of the avalanche, the worse the flow of the material. It was found that the flowability remained constant with the addition of 0 to 30 wt. % of silane.

[0160] In the case of silane GLYEO above 30 wt%, the avalanche angle decreases with increasing silane proportion, from about 60° to below 50° at 50 wt% silane GLYEO. Thus, it is found that by adding more than 30 wt% silane GLYEO, the flowability is significantly improved.

[0161] Figure 8 The camera images recorded on the Revolution Powder Analyzer at the moment of avalanche formation are shown for respective functionalized graphene materials of the present invention for different mass fractions of the silane GLYEO.

[0162] In order to study the stability of the graphene material prepared according to the present invention after a long operation, the mixing program of Revolution Analyzer was used, and the operation duration was 5.8 hours. This program includes 150 cycles of alternating a period of 20 seconds of relatively fast mixing at 5 rpm with a period of 120 seconds of slower mixing at 1 rpm.

[0163] After the procedure is completed, the flowability is measured again as described above. Fig. 9 As shown in , the average avalanche angle of the unfunctionalized graphene material increased significantly from 59° to 64°, indicating worse fluidity.

[0164] In contrast to the above, the avalanche angle of the graphene material functionalized according to the invention with the silane GLYEO does not increase at all or hardly increases after prolonged mixing.

[0165] Another indicator of the flowability of the graphene material is the avalanche energy, which is also measured. The lower the energy at the beginning of the avalanche, and the smaller the change in avalanche energy with the change in the mass fraction of silane, the better the flowability of the material.

[0166] exist Fig.10 In the Figure 1, it can be seen that the best results are obtained at about 30 to 35 wt. % silane GLYEO.

Claims

1. A method for functionalizing a graphene material, the method being characterized in that: at least partially reacting the graphene material with at least one silane, wherein the at least one silane has the structure Y—Si(OR 1 )(OR 2 )(OR 3 ),and Y is: branched or unbranched alkyl groups, olefin groups or aromatic groups, combinations of these groups, or a functional organic group selected from carboxyl, carbonyl, hydroperoxycarbonyl, halogen, sulfo, sulfinic acid, hydroxythio, cyano, formyl, oxo, thio, hydroxy, amino, imino, hydrazine, epoxy, sulfanyl, fluoro, or a combination of these groups; or a combination of an alkyl, olefin or aromatic group and said functional organic group, and R 1 , R 2 , R 3 are branched or unbranched alkyl, olefin or aromatic groups, which are identical or different to each other, and the at least partial reaction is carried out during mixing the one or more silanes with the graphene material, wherein the mixing process uses a mixing granulator, a container with grinding balls, a ball mill, a three-roll mill, a stirrer or a container equipped with a paddle; wherein the sum of the mass fractions of the at least one silane is in the range of 5 wt % to 40 wt %, and wherein the sum of the mass fractions of the one or more silanes and the graphene material is 100 wt %.

2. The method according to claim 1, wherein two or more silanes are used, in which Y or R 1 , R 2 , R 3 Are two identical or different.

3. The process according to claim 1, wherein the at least one silane is selected from 3-glycidyloxypropyltriethoxysilane, 3-aminopropyltriethoxysilane, glycidyloxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane and mixtures of these silanes.

4. The method according to any one of claims 1 to 3, wherein the sum of the mass fractions of the at least one silane is in the range of 25% to 40% by weight, and wherein the sum of the mass fractions of the one or more silanes and the graphene material is 100 wt %.

5. The method according to any one of claims 1 to 3, wherein the at least partial reaction is carried out at a temperature in the range of 50°C to 150°C.

6. The method of claim 5, wherein the at least partial reaction is carried out at a temperature in the range of 80°C to 110°C.

7. A functionalized graphene material obtained by the method according to any one of claims 1 to 6, characterized in that Bulk density is 300 g / L to 900 g / L, and / or, The compacted density is 300 g / L to 900 g / L, and / or, Dust generation reduction rate is 50% to 80%.

8. The functionalized graphene material according to claim 7, characterized in that Bulk density is 500 g / L to 800 g / L, and / or, The compacted density is 500 g / L to 800 g / L, and / or, Dust generation reduction rate is 55% to 75%.

9. Use of the functionalized graphene material according to claim 7 or 8 as filler, as corrosion protection in coatings, for anti-icing, as active material and / or electrode material in batteries, in composite materials and / or foams for modifying mechanical, thermal, electrical and tribological properties and flame retardancy, in tire rubbers, in transmission oils and / or engine oils, in metal processing, or in membranes.

10. The use according to claim 9, wherein the functionalized graphene material is used in: thermoplastics selected from standard thermoplastics, engineering thermoplastics, and high-performance thermoplastics; rubber; Thermosetting plastics; or Solvent.

11. The use according to claim 10, wherein the functionalized graphene material is used in: PE, PP, PS, PVC, PET, PMMA, PC, POM, PA, PPS, PEEK, PES or polyurethane.

12. The use according to claim 9, wherein the functionalized graphene material is used in a copolymer.

13. The use according to claim 9, wherein the functionalized graphene material is used in an elastomer.

14. Use according to claim 13, wherein the elastomer is silicone.

15. Use according to claim 14, wherein the silicone is selected from RTV, HTV and LSR.

16. The use according to claim 10, wherein the rubber is selected from SBR, BR and natural rubber.

17. The method according to claim 10, wherein the thermosetting plastic is selected from the group consisting of polyurethane, polyester resin, phenolic resin, epoxy resin, acrylate resin and silicone resin.

18. The use according to claim 10, wherein the solvent is an aprotic-nonpolar solvent, an aprotic-polar solvent or a protic solvent.

19. The use according to claim 9, wherein the functionalized graphene material is used in oil.

20. Use according to claim 19, wherein the oil is selected from mineral oil, silicone oil and process oil.

Citation Information

Patent Citations

  • Dustproof and bactericidal type aqueous coating material for glass doors and preparation method thereof

    CN104342003A

  • Composite spherical activated carbon added with polyester fibers and capable of improving mechanical strength as well as preparation method of composite spherical activated carbon

    CN105056879A

  • Composite graphene pre-dispersion masterbatch and preparation method thereof

    CN107459717A

  • Fluorosilicon self-leveling antifouling material and preparation method thereof

    CN108947394A

  • sPS (syndiotactic polystyrene) film for FPC (Flexible Printed Circuit) industry and preparation method thereof

    CN109504318A